Village Head Leadership in The Implementation of The Village Development Movement Program in Malinau Barat Sub-District, Malinau Regency - Maksuwel, Maksuwel; Adhy Muhtar, Entang; Wahyudi, Heri (Jurnal Locus Penelitian dan Pengabdian, 2025)
To realize the Building Village Movement (GERDEMA) in West Malinau District, Malinau Regency, it is necessary to have the leadership of the Village Head who is sensitive, must listen to suggestions and views from the people around him, must be an example, must behave and be loyal to his promises, be loyal to his government and be able to make decisions, in accordance with the ideals and expectations of the community. The purpose of this study is to describe and analyze how the Village Head Leadership in the implementation of the Building Village Movement Program (GERDEMA) in West Malinau District, Malinau Regency. Problems in the leadership of the Village Head in general have been carried out, but in reality they have not been fully carried out optimally. The method used is a qualitative method to explore and understand the meaning of individuals or groups related to social or humanitarian issues. The goal of this qualitative research is to understand certain situations, events, roles, groups or social interactions that are considered to be social problems. The results of the research show that the leadership of the Village Head in the implementation of the Building Village Movement Program in West Malinau District can be carried out well, the Village Head has good sensitivity, has an exemplary spirit that can be used as an example, has good compliance in the implementation of programs in the village and has a leadership spirit and integrity in the implementation of the Building Village Movement (GERDEMA) program.